Relationship between technological change, digitization, and students' attitudes toward distance learning in Lagos Higher Education institutes - Joy Onyekwere; Kazi Enamul Hoquei (Universidad de Málaga, 2023)
The focus of this research is to investigate the relationship between learning flexibility, support services, and students' attitudes toward remote learning programs in Nigeria. A correlational research methodology is used, and 385 individuals drawn from a multi-stage sampling technique form the study's sample. The data collecting tool is a three-section questionnaire devised by the researchers. Experts validated the questionnaire, which was then administered once on a randomly selected sample to assess the internal consistency. The Cronbach Alpha formula produced values of .74, .77, and .78 for the three separate questionnaire constructs. At the .05 level of significance, two research questions were posed, and two related null hypotheses were investigated. The collected data is analysed using the Mean, Standard Deviation, and Pearson Product Moment Correlation formulas. The findings show that there is a positive relationship between digital learning flexibility and students' attitudes toward distant learning programs (r =.439, Freq=476, p.05). There is also a favourable link between technology supports and students' attitudes toward distant learning programs (r =.339, Freq=476, p.05). It is thus recommended, among other things, that providers of distance learning programs guarantee high flexibility and quality learner support services to cater to the academic needs of learners with different characteristics, as this would improve students' positive attitudes and increase the enrolment of candidates in distance learning programs.